2023
DOI: 10.6004/jnccn.2023.0020
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines® Insights: Non–Small Cell Lung Cancer, Version 2.2023

Abstract: The NCCN Guidelines for Non–Small Cell Lung Cancer (NSCLC) provide recommendations for management of disease in patients with NSCLC. These NCCN Guidelines Insights focus on neoadjuvant and adjuvant (also known as perioperative) systemic therapy options for eligible patients with resectable NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
108
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(108 citation statements)
references
References 29 publications
0
108
0
Order By: Relevance
“…MRI or CT with contrast are normally recommended for evaluating brain metastases [31]. For example, in nonsmall cell lung cancer patients, National Comprehensive Cancer Network recommended MRI brain for evaluation for clinical stage II disease or above [31].…”
Section: Potential Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI or CT with contrast are normally recommended for evaluating brain metastases [31]. For example, in nonsmall cell lung cancer patients, National Comprehensive Cancer Network recommended MRI brain for evaluation for clinical stage II disease or above [31].…”
Section: Potential Impactmentioning
confidence: 99%
“…MRI or CT with contrast are normally recommended for evaluating brain metastases [31]. For example, in nonsmall cell lung cancer patients, National Comprehensive Cancer Network recommended MRI brain for evaluation for clinical stage II disease or above [31]. As delays in detecting asymptomatic brain metastases may compromise disease control and increase mortality, some have expressed concerns that the brain may be under-imaged [32].…”
Section: Potential Impactmentioning
confidence: 99%
“…In 2022, the Food and Drug Administration (FDA) approved neoadjuvant nivolumab with platinum-doublet chemotherapy for patients with resectable NSCLC based on results of the Phase III CheckMate 816 trial . This approval led to a recommendation by the National Comprehensive Cancer Network for neoadjuvant nivolumab with platinum-doublet chemotherapy in patients with stage IB to IIIA or IIIB (only T3, N2) NSCLC . In 2023, the FDA approved neoadjuvant pembrolizumab in combination with platinum-containing chemotherapy for resectable NSCLC followed by single-agent pembrolizumab in the adjuvant setting across all programmed cell death 1 ligand 1 (PD-L1) strata after overall survival (OS) results were produced from KEYNOTE-671 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Nevertheless, the treatment strategy for advanced lung cancer remains contentious due to the complexity and heterogeneity of tumors. 4 Recent studies have suggested that neoadjuvant immunotherapy, either alone or in combination with chemotherapy, significantly improves the prognosis of patients with middle to advanced stage resectable lung cancer. [5][6][7] In cases of unresectable advanced lung cancer, the primary treatment strategies involve concurrent or sequential radiotherapy and immunochemotherapy.…”
Section: Introductionmentioning
confidence: 99%